Who are those new entrants? dissecting types of foreign capital entrance in traditional industrial districts - Hervas-Oliver, José Luis; Boronat-Boll, Carles; Peris-Ortiz, Marta; Rojas Alvarado, Ronald (My University, 2023)
This paper explains the effects originated by the massive entrance of foreign capital in the ceramic tile district of Castellon (Spain). Cross-fertilizing multinational acquisitions and industrial districts’ literature, and using mix-methods on a focal case study, our article explores the effects that those multinationals have on districts, and whether the type of multinationals (financially-oriented vs industrial) presents different impacts on a focal industrial district. Our results point out that the massive entrance of foreign capital alters the local system. Overall, positive perceived attitudes are evidenced, along with negative attitudes associated with potential risks of lack of local-embedded ownership and the reduction of local cooperative ties.
European Planning Studies
Keywords: Industrial districts; Innovation; Private equity; Multinationals; Acquisitions; Campus Tijuana